Answer:
Multiply the second equation by 3 and then add result to the first equation
Explanation:
Given the equations :
x-3y=2
{2x+y=11
To solve by elimination :
Multiply one of either equations by a number to give a result such that adding the result to the other equation in the system leads to the removal of one of the unknown values.
By Multiplying the second equation by 3 and then add result to the first equation
Second equation becomes :
6x + 3y = 33
Adding the result to the first equation :
x - 3y = 2
6x + 3y = 33
___________
7x = 35
_________
Here, the y variable has been eliminated